The Effect Of Woolwich Massage On Breast Milk Production In Post Partum Mothers At The Pratama Sejahtera Clinic In 2024 - Lormita Purba (International Journal of Health and Social Behavior, 2025)
Woolwich Massageis a massage performed on the lactiferous sinus exactly 1-1.5 cm above the areola mammary, with the aim of removing breast milk in the lactiferous sinus. The massage will stimulate the nerve cells in the breast. From the interview results, it was found that there were postpartum mothers who did not know about Woolwich Massage and its benefits at the Pratama Sejahtera Clinic. The research method uses the Chi-Square test. The population and sample of this research are25 postpartum mothers underwent Woolwich Massage at the Pratama Sejahtera Clinicusing total sampling technique. The data used are primary and secondary data. Univariate and bivariate data analysis using the Chi-Square test. The results of the study indicate that there is an Effect of Woolwich Massage on Breast Milk Production in Postpartum Mothers at the Pratama Sejahtera Clinic in 2024 with a degree of significance (α) = 0.05 and df = 1, the calculation results are Sig. (2-tailed) 0.000 <(α) = 0.05, then Ho is rejected and Ha is accepted. The conclusion is that there is an effect of Woolwich Massage on Breast Milk Production in Postpartum Mothers. It is hoped that postpartum mothers can carry out Woolwich Massage more routinely to increase breast milk production.